Blood pressure response to CPAP treatment in subjects with obstructive sleep apnoea: the predictive value of 24-h ambulatory blood pressure monitoring. Issue 4 (5th October 2017) - Castro-Grattoni, Anabel L.; Torres, Gerard; Martínez-Alonso, Montserrat; Barbé, Ferran; Turino, Cecilia; Sánchez-de-la-Torre, Alicia; Cortijo, Anunciacion; Duran-Cantolla, Joaquin; Egea, Carlos; Cao, Gonzalo; Sánchez-de-la-Torre, Manuel
The reduction in blood pressure (BP) with continuous positive airway pressure (CPAP) is modest and highly variable. In this study, we identified the variables that predict BP response to CPAP. 24-h ambulatory BP monitoring (ABPM), C-reactive protein (CRP), leptin, adiponectin and 24-h urinary catecholamine were measured before and after 6 months of CPAP in obstructive sleep apnoea (OSA) patients. Overall, 88 middle-aged, obese male patients with severe OSA (median apnoea–hypopnoea index 42 events·h −1 ) were included; 28.4% had hypertension. 62 patients finished the study, and 60 were analysed. The daytime diastolic BP (−2 mmHg) and norepinephrine (−109.5 nmol·day -1 ) were reduced after CPAP, but no changes in the 24-h BP, night-time BP, dopamine, epinephrine, CRP, leptin or adiponectin were detected. The nocturnal normotension was associated with an increased night-time-BP (+4 mmHg) after CPAP, whereas nocturnal hypertension was associated with a reduction of 24-h BP (−3 mmHg). A multivariate linear regression model showed differential night-time BP changes after CPAP. Specifically, low night-time heart rate (<68 bpm) and BP dipper profile were associated with increased night-time BP and new diagnosis of nocturnal hypertension. Our results suggest that nocturnal hypertension, circadian BP pattern and night-time heart rate could be clinical predictors of BP response to CPAP and support the usefulness of 24-h ABPM for OSA patients before treatment initiation. These results need to be confirmed in further studies. 24-h ambulatory blood pressure monitoring showed predictive value for the blood pressure response to CPAP treatment http://ow.ly/Wuf230dqP4T